Bellavista: Political Incorporation in a Columbian Urban Barrio - Robertson, Peter R. (Culture, 1981)
The locus of the study is an established lower-class mestizo neighbourhood (formerly a squatter settlement) on the margin of a city in the coffee-producing departamento of Caldas, Columbia. The residents exhibit considerable diversity in productive occupations, including both rural and urban, skilled and unskilled labour. The political behaviour of barrio residents appears as several isolated networks between which there is very little interaction. While general distrust in the benefits of political participation is a commonly-expressed sentiment, on an individual basis vertical patronage hierarchies which channel jobs and favours in exchange for votes are an important social mechanism incorporating the barrio residents into national political activities. But these vertical networks significantly increase the difficulty of achieving concensus in working toward community goals. The role of the political broker is central to the ongoing formation of political attitudes in the barrio.